(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study was undertaken to assess the diet nutrient intake and nutritional status adolescent girls of 18 to 19 years who attend the Arts and Commerce Mahila Mahavidyalay from Ambajogai town. Nutritional status of selected adolescent girls was assessed by recording anthropometric measurements, clinical examination and diet survey. Majority of selected adolescent girls were from middle socio economic zone having few family members. Adolescent girls who are surveyed having normal weight and height but the girls of above 19 age we are found to under nourish as per BMI. Bleeding gums was found to be the most common clinical sign among selected girls followed by angular stomatitis and muscular cramps. Intake of all type of vegetable fruits and milk and Milk products was markedly low. Even the intake of serial and pulses where inadequate by 10 and 20% respectively in the diet of adolescent girls. The diet of adolescent girls was found inadequate in providing all essential nutrients. Thus, there is need to supplementation of diet of adolescent girls to improve their nutritional status